Towards understanding host–pathogen dynamics of cetacean poxvirus: attainable approach through the application of a repetitive non-invasive skin sampling in bottlenose dolphins (Tursiops truncatus) under human care - Segura-Göthlin, Simone; Fernández, Antonio; Arbelo, Manuel; Almunia, Javier; von Fersen, Lorenzo; Baumgartner, Katrin; Garcés, José Guerra; Llanos, Aldo Gutiérrez; Felipe-Jiménez, Idaira; Colom-Rivero, Ana; Sierra, Eva (Frontiers in Marine Science, 2023)
Nowadays, zoos and aquariums, along with the constant advancement of sociocultural moral values, are proactively committed to ensuring and safeguarding cetacean health standards. This entails developing new approaches to health assessments by embracing minimally invasive sampling methods and enhanced animal handling and management, among other aspects. Hence, in the present survey, to appraise skin diseases, the implementation of cytology cell samplers as a non-invasive skin sampling device on 18 bottlenose dolphins housed in two facilities in the Canary Islands during the months of April, October, and December 2019 was performed to isolate cetacean poxvirus in tattoo-like lesions through a real-time PCR-based method using the DNA polymerase gene. Samples were repeatedly collected over time from eleven tattoo-like lesions and from apparently healthy skin to serve as a control for all study animals. From a total of 55 skin samples, detection of the poxvirus was attained in 31 (56.36%); specifically, on 20 of 21 samples collected from tattoo-like lesions (95.23%) and on 11 of 34 samples acquired from apparently healthy skin (32.35%). Correspondingly, the current study constitutes the first report of the isolation of cetacean poxvirus in skin samples without macroscopical signs of tattoo lesions in cetaceans. Likewise, ten of the eleven dolphins that showed tattoo lesions housed in Facility 1 were positive for tattoo skin disease, while four dolphins held in Facility 2 were positive for cetacean poxvirus without ever showing clinical evidence of the disease. This raises the question of whether this pathogen can produce latent infections and whether progression of the disease may depend on environmental stimuli, viral load, or the good health/immunological status of individual animals. Accordingly, further scientific research on cetaceans under human care could provide the knowledge, skills, and resources to understand the host–pathogen dynamics of cetacean poxviruses and their effect on cetaceans’ health.